Energetic Potential of the Biogas from Urban Solid Waste Generated in the Jacareí Municipal landfill, Brazil (Global Journal of Science Frontier Research, 2022)
The use of biogas from solid waste is a way to produce renewable and clean electric energy and presents itself as an alternative to make up the country's energy matrix as well as a solution to the serious problem faced by municipalities that is the accumulation of waste. In this article it was evaluated the potential of the biogas from the landfill of the municipality of Jacarei which has an estimated population of 277,800 inhabitants and a daily waste volume of around 140 ton/day. From the estimated volume of biogas produced in the landfill, about 11.43 million m 3 /year at maximum production, the annual electricity generation value was 3.81 GWh. However, based on the scenarios and assumptions adopted, a possible project implementation would not be economically viable. The study reinforces that a minimum amount of waste is needed to enable this alternative as energy production purpose, but encourages other assessments within existing conversion technologies as well as signaling the need for incentives and policies that make such projects viable. The positive result of the study is achieved when the greenhouse gas emissions (GHG) avoided is analyzed, since methane (CH 4 ) and carbon dioxide (CO₂) are gases that most contributes to the GHG effect.
Keywords: waste to energy (WtE); global warming; clean development mechanism (CDM); power generation